Between Environmental Performance and Agricultural Productivity: Assessing the Convergence and Divergence of Demand-Driven Agricultural Extension - Widayati, Tri; Waridin, Waridin; Mafruhah, Izza (International Journal of Energy Economics and Policy, 2019)
This study aims to analyze and evaluate the implementation of agricultural extension on bridging the critical point between environmental performance and agricultural productivity based on community needs and the role of agricultural extension in increasing productivity, reducing the number of poor and environmental degradation. This research uses sequential mixed method with stakeholder analysis and descriptive statistics. This research was conducted on 31 samples of farmer groups in Kejajar Subdistrict, in Dieng plateau area, Central Java Province. The results showed that the level of effectiveness of farmer group participation was classified as medium. The role of stakeholders and academics is still low, but the role of agricultural extension officers is relatively high because they are more responsive to the farmers’ needs. The implementation of agricultural extension in Dieng area has not fully utilized demand driven basis due to institutional and regulatory factors that have not fully supported the role of agricultural extension officers in the field. In addition, it is also found that the competence of agricultural extension officers is still low so that they have not been able to carry out demand-driven extension function. Keywords: Agricultural Extension, Potato Farming, Demand-Driven, Food Productivity, Environmental Quality JEL Classifications: O13, Q16 DOI: https://doi.org/10.32479/ijeep.7688